Analysing fluency in writing among the Malay bilingual learners in UK and Malaysia - Jalaluddin, Ilyana (European Centre for Research Training and Development UK, 2018)
This study investigated how much variation in narrative writing fluency can be explained by the predictor variables namely age, residence and fluency in argumentative writing. The participants were 92 Malay bilingual learners aged 8 to 13 years old and living in United Kingdom (UK) or Malaysia. Both groups wrote two different writing tasks differing in genre for the purpose of the study. A multiple regression was run to predict the fluency in narrative writing from age, fluency in argumentative essay and location of residency. The multiple regression model statistically significantly predicted fluency in narrative writing F(3,88)=61.898, p<.0005, adj. R2=.668. All four variables added statistically significantly to the prediction, p>.05. The findings are discussed in light of the factors contributing to the fluency in writing among bilingual learners.